A Literature Review: Transformational leadership style Analysis - Selvira Bawotong; Andi Indriani Ibrahim; Syahbudin Adam; Sahra S. T. Ali; Yuliana; Yuliana Tamsil; Zahra Aulia Tanjung (Universitas Muhammadiyah Palu, 2025)
The dramatic changes in the business environment due to globalization, technological advancements, and intensified competition have